Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00432-021-03851-9
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry correlates to presenting symptoms and mortality in uveal melanoma

Abstract: Purpose Fluid-conducting extracellular matrix patterns known as vasculogenic mimicry (VM) have been associated with poor prognosis in uveal melanoma and other cancers. We investigate the correlations between VM, presenting symptoms, mortality, and the area density of periodic acid-Schiff positive histological patterns (PAS density). Methods Sixty-nine patients that underwent enucleation for uveal melanoma between 2000 and 2007 were included. Clinicopatholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…For example, gene expression class, BAP1, SF3B1, EIF1AX, and chromosome 3 status, presence or absence of vasculogenic mimicry, and tumor cell type are all important prognostic factors that were not accounted for herein. [44][45][46][47][48][49] Mutations in SF3B1 have been associated with late onset of metastases at a median of 8 years after diagnosis but no sex predilection has been observed in previous studies. [50][51][52] The reader should be aware that the worse survival for women in the second decade after UM diagnosis and beyond is not necessarily caused by increased presence of a poor prognostic factor in the women surviving ≥10 years.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, gene expression class, BAP1, SF3B1, EIF1AX, and chromosome 3 status, presence or absence of vasculogenic mimicry, and tumor cell type are all important prognostic factors that were not accounted for herein. [44][45][46][47][48][49] Mutations in SF3B1 have been associated with late onset of metastases at a median of 8 years after diagnosis but no sex predilection has been observed in previous studies. [50][51][52] The reader should be aware that the worse survival for women in the second decade after UM diagnosis and beyond is not necessarily caused by increased presence of a poor prognostic factor in the women surviving ≥10 years.…”
Section: Discussionmentioning
confidence: 91%
“…Other than the potential dissimilarity in hormonal and reproductive factors, it is fully possible that there were differences in other established predictors. For example, gene expression class, BAP1, SF3B1, EIF1AX , and chromosome 3 status, presence or absence of vasculogenic mimicry, and tumor cell type are all important prognostic factors that were not accounted for herein 44–49 . Mutations in SF3B1 have been associated with late onset of metastases at a median of 8 years after diagnosis but no sex predilection has been observed in previous studies 50–52 .…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that patients presenting with a shadow in the visual field have significantly shorter disease‐specific survival, regardless of other symptoms, tumour size, location, local extent and stage (Fili et al, 2020 ). In turn, tumours from UM patients that report a visual field shadow are more likely to display vasculogenic mimicry and greater density of PAS positive patterns, which may underpin the association between this symptom and poor prognosis (Sabazade et al, 2021a , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…One exception is a large study by Kujala et al ( 2013 ), who found that tumour diameter, tumour thickness, CBI and extraocular extension were all independent predictors of melanoma‐related mortality in multivariate Cox regression (Kujala et al, 2013 ). In contrast to iris melanomas who have no better prognosis than choroidal melanomas when adjusting for tumour diameter and thickness, this should make it unlikely that increased tumour size is the real reason for the prognostic implication of CBI (Johansson et al, 2020 ; Sabazade et al, 2021a , 2021b ). The American Joint Committee on Cancer (AJCC) classification of UM consequently assigns tumours with CBI a subcategory with shorter metastasis‐free survival (Kujala et al, 2013 ; Kujala & Kivela, 2005 ; Simpson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the VM area, the CD31/PAS stained slides were scanned by low power to identify areas which are positive for VM, and then five images at high-power field (×400) were captured. The VM area was recorded in these five high-power fields (400×) using open-access ImageJ and then averaged [ 22 ].…”
Section: Methodsmentioning
confidence: 99%